Multiple Birthdating Analyses in Adult Neurogenesis: A Line-Up of the Usual Suspects - LLorens-Martín, María; Trejo, José Luis (Frontiers in Neuroscience, 2011)
Analyzing the variation in different subpopulations of newborn neurons is central to the study of adult hippocampal neurogenesis. The acclaimed working hypothesis that different subpopulations of newborn, differentiating neurons could be playing different roles arouses great interest. Therefore, the physiological and quantitative analysis of neuronal subpopulations at different ages is critical to studies of neurogenesis. Such approaches allow cells of different ages to be identified by labeling them according to their probable date of birth. Until very recently, only neurons born at one specific time point could be identified in each experimental animal. However the introduction of different immunohistochemically compatible markers now enables multiple subpopulations of newborn neurons to be analyzed in the same animal as in a line-up, revealing the relationships between these subpopulations in response to specific influences or conditions. This review summarizes the current research carried out using these techniques and outlines some of the key applications.